Disability weight for each level of the Expanded Disability Status Scale in multiple sclerosis. (August 2014) - Cho, Joong-Yang; Hong, Keun-Sik; Kim, Ho Jin; Kim, Su-Hyun; Min, Ju-Hong; Kim, Nam-Hee; Ahn, Suk-Won; Park, Min Su; An, Jae-Young; Kim, Byung-Jo; Kim, Woojun
Background: The Expanded Disability Status Scale (EDSS) is the most widely employed ordinal disability scale in multiple sclerosis (MS). However, how far apart the individual EDSS levels are along the disability spectrum has not been formally quantified. Objectives: The objective of this paper is to generate refined disability weights (DWs) for each of the ordinal EDSS levels. Methods: We performed the person trade-off (PTO) procedure to derive DWs of five representative EDSS categories (2, 4, 6, 7 and 9), and DWs of the remaining EDSS categories were assigned by linear interpolation. The modified Delphi process was used to achieve consensus among raters. Results: DWs were 0.021 for EDSS 2, 0.199 for EDSS 4, 0.313 for EDSS 6, 0.617 for EDSS 7, and 0.926 for EDSS 9. Panel members achieved a high degree of consensus for each DW, as indicated by low coefficients of variation. Conclusions: Our DWs confirmed that EDSS is an ordinal scale with highly variable intervals. The availability of DW for each EDSS level allows direct comparison of each MS outcome state with other health states and provides a foundation for the estimation of the disability-adjusted life-years lost of individual patients.